Participatory Development Reconsidered - Mansuri, Ghazala (2012)
Over the last two decades development policy has touted civic participation as a magic bullet for solving problems at the local level from improving livelihoods, to selecting beneficiaries for public programs, providing housing after earthquakes and floods, or improving village infrastructure. The thinking is that involving village or urban civic communities in decision making will improve accountability, reduce inequality, and ultimately alleviate poverty.